Integration of the Information Adoption Model and Theory of Planned Behavior in Predicting the Intention to Register for BPJS Ketenagakerjaan in the Non-Wage Earner Segment (BPU) - Maharani, Dewi; Sumarwan, Ujang; Sufrin, Sufrin (Pelopor Publikasi Akademika, 2026)
This study integrates the Information Adoption Model (IAM) and Theory of Planned Behavior (TPB) to predict the intention to register for BPJS Ketenagakerjaan in the Non-Wage Earner (BPU) segment. Primary data were collected through a questionnaire survey of 250 respondents working in the agriculture, forestry, and fisheries sectors who were not yet registered with BPJS Ketenagakerjaan Sampit Branch but followed BPJS Ketenagakerjaan social media. Data analysis employed Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS 3 software. The analysis results indicate that information quantity and information credibility significantly influence information usefulness, while information quality does not have a significant effect. Information usefulness significantly influences information adoption, which in turn affects purchase intention. The TPB variables—attitude toward behavior, subjective norm, and perceived behavioral control—all significantly influence purchase intention. Furthermore, information adoption mediates the relationship between information usefulness and purchase intention. These findings suggest that improving the quantity and credibility of information, along with strengthening positive attitudes, social support, and perceived ease of registration, can enhance information adoption and registration intention for BPJS Ketenagakerjaan among the BPU segment. The study contributes to the theoretical integration of IAM and TPB in the context of social security services for informal workers.